Virtual Reality and Multimedia Research Group (GRVM) - Kelner, Judith; Ferreira, André M; Vasconcelos, Luis (Journal on Interactive Systems, 2011)
This paper briefly describes the Virtual Reality and Multimedia Research Group – GRVM –, its research lines, projects and some publications. The group, founded in 1998 at the Federal University of Pernambuco – UFPE – is already a national reference when it comes to scientific and academic research in computer science, especially as for the GRVM’s main areas of interest, and it moves towards to international recognition.